Kinetic study of the thermal decomposition of cellulose nanocrystals with different polymorphs, cellulose I and II, extracted from different sources and using different types of acids - Henrique, Mariana Alves; Flauzino Neto, Wilson Pires; Silverio, Hudson Alves; Martins, Douglas Ferreira; Alves Gurgel, Leandro Vinicius; Barud, Hernane Da Silva [UNESP]; Morais, Luis Carlos de; Pasquini, Daniel (Elsevier B.V., 2015)
Cellulose nanocrystals (CNs) were extracted from different sources by acid hydrolysis using H2SO4 and HCI. The thermal decomposition of resulting CNs was studied by thermogravimetric analysis (TGA). The kinetic parameters were determined using the Flynn-Wall-Ozawa (FWO) and Kissinger methods. CNs were also characterized by X-ray diffraction (XRD), Atomic Force Microscopy (AFM), elemental analysis (EA), Zeta Potential (ZP) and degree of polymerization (DP). The results of the XRD analysis showed different profiles, making it possible to differentiate cellulose I from cellulose II. The results obtained by the FWO method showed that cellulose II CNs had an increased activation energy (E-a) with conversion (alpha), while in CNs of cellulose I the E-a remained constant or decreased slightly. This difference between E-a values for the thermal decomposition of CNs was mainly attributed to different crystalline arrangements of cellulose land cellulose II, and to the type of acid employed. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Cellulose nanocrystals; Thermal decomposition; Decomposition kinetics; Kissinger; Flynn-Wall-Ozawa